(untitled) (Interdisciplinary Studies Journal, 2025)
How to teach mathematics to students deprived of liberty during social distancing due to the coronavirus pandemic, SARS-CoV2? This challenge gave rise to research aimed at investigating the movement of mathematical thinking during the formation of knowledge about the multiplicity relationship. To this end, an investigative didactic experiment was carried out with students of Youth and Adult Education in a public penitentiary located in Sertão, Paraíba, Brazil. The didactic experiment was organized based on Davydov’s Theory of Developmental Teaching and Moura’s Teaching Guiding Activity. Due to the pandemic, there was no physical contact with the students. Communication was carried out only in writing, through a notebook for each student. The tasks were printed on A4 sheets and pasted into the notebooks. The students collectively reflected on each task and responded individually in their respective notebooks. The data source consists of the students’ handwritten responses. The analysis process revealed evidence of the completion of abstraction, generalization, and conceptual formation procedures at the theoretical level.